Idiopathic Ascites after Laparoscopic Appendicectomy: a review of literature and a case report (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Minimal access surgery, encompassing laparoscopy and robotic procedures, has become the preferred choice for a wide range of surgical interventions, receiving widespread acceptance from both surgeons and patients. However, as the utilization of these minimally invasive techniques continues to grow, surgeons are increasingly confronted with unforeseen and puzzling complications. One such rare and perplexing complication is the emergence of ascites following laparoscopic procedures, particularly when no accidental injury to the bowel or urinary system has occurred, posing a challenging and distressing scenario for the operating surgeon.Aims and Objective:We have encountered a case of idiopathic ascites following a laparoscopic appendicectomy in a 10-year-old boy. The primary objective of this study is to conduct a comprehensive literature review to identify similar case reports and publications. By doing so, we aim to enhance our understanding of the causes and principles for managing idiopathic ascites occurring after laparoscopic surgery.Methods: A 10-year-old boy was admitted to the hospital with typical symptoms of acute appendicitis. Following evaluation, a nearly bloodless and uneventful laparoscopic appendicectomy was performed. However, postoperatively, he developed ascites accompanied by scrotal swelling due to scrotal edema, and despite thorough evaluation, no identifiable cause was found. The patient was managed conservatively and fully recovered without any subsequent complications.Results: The occurrence of ascites stemming from an idiopathic allergic or inflammatory peritoneal reaction during a laparoscopic procedure is exceptionally rare. During the patient's evaluation, the paramount concern was to rule out potentially significant complications such as bowel or urinary tract injuries, which can commonly result in postoperative peritoneal fluid accumulation. After the procedure, the boy underwent a thorough evaluation, but no definitive cause for the ascites was identified, further highlighting the enigmatic nature of this condition.Conclusion: Postoperative ascites without a discernible cause following laparoscopic surgery is an unexpected complication. In such cases, the leading hypothesis points to a peritoneal inflammatory reaction induced by agents utilized during laparoscopy.J Bangladesh Coll Phys Surg 2024; 42: 194-198